Calculation Model for Optoelectronic Remote Sensing System’s Radiometric Resolution at Arbitrary Viewing Angles (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2017)
Introduction. One of the urgent problems, which are facing developers of satellite optoelectronic remote sensing systems (ORSS), is to improve the images quality. Image quality is determined, above all, by its radiometric resolution, which means minimum difference between brightness or reflectivity of object and background, which can be detected by ORSS with a given probability. Modern ORSS make possible viewing angle deviation, which causes significant image distortions. Formulation of the problem. The purpose of the paper is to develop physical and mathematical radiometric resolution model of satellite remote sensing optoelectronic systems at arbitrary sight angles. Video signal formation model and radiometric resolution study. Solar radiation that is reflected from the Earth's surface on which the object of observation is placed, passes through atmosphere and enters into transmitting camera lens. The lens forms image of the object and the background radiation in the detector plane. Detector converts illuminance distribution to electric signal, which forms video signal after scanning. The object of observation has uniform spectral reflectance over its size and its angular size is much bigger than ORSS instantaneous field of view. The object is situated on Earth’s surface with uniform spectral reflection coefficient. Both object and background reflect light on Lambert's law. An example of ORSS radiometric resolution calculation model was considered. Conclusions. On the basis of proposed optoelectronic remote sensing system model there was developed method of determination its radiometric resolution at arbitrary angles of sight. Study of the model showed that, increasing of viewing angle significantly deteriorates optoelectronic system spatial resolution while the radiometric resolution is unchanged.